Composite generation and transmission system reliability evaluation including system health constraints - Low, William Long Shun. (2008)
This research project is aimed at establishing the well-being analysis of composite power systems. The well-being analysis is first explained, with the definition of the various states and their calculation methods. The framework is then used to perform various sensitivity studies and the results of these studies are discussed to illustrate the usefulness and the information that can be gained from such analysis.